Nilai Sufistik Pembudayaan Musik Shalawat Emprak Pesantren Kaliopak Yogyakarta - Zamzami, Mukhammad (MarÃƒÂ¢ji`: Jurnal Ilmu Keislaman, 2015)
This article explores the culture of music in the tradition of Shalawat Emprak in Pesantren Kaliopak Yogyakarta from the perspective of Sufism. Essentially, Shalawat Emprak is similar to the Sufi tradition of listening to music (samÃ¢â) as one of the media to draw closer to God. The music is, however, regarded merely as a medium, but it is not a primary mean. Shalawat Emprak is different from classical Sufism, which emphasizes personal behavior towards God. In the context of Sufi thought, Emprak seems more like a Sufi order (tarekat), in which an activity carried congregation. The process towards God congregation in Emprak is reinforcing efforts and build resonance, so as to strengthen each individual and accelerate the process toward God. Every soul can actualize the unique path to God, one of them through tradition of Shalawat Emprak. This is because the path to God is not only found in the mosque or other places of worship, but also in the humanâs soul. Therefore, it is an important matter to create conditions, pre-conditions, and social relationships which stimulate and encourage a person to find a way to God.